Controlled Growth of ZnSe Nanocrystals by Tuning Reactivity and Amount of Zinc Precursor - Lai-Jun Zhang; Fa-Yun Chen; Ji-Zao Tong; Guang-Da Chen; Hai-Jin Huang; Xing-Can Shen (Journal of Chemistry)
Zinc selenide (ZnSe) nanocrystals were synthesized via a phosphine-free route using the highly reactive alkylamine-H2Se complex as selenium precursor and zinc precursors with different reactivity. The reactivity of zinc precursor was tuned by using three kinds of zinc carboxylates with different alkyl chain lengths, including zinc acetate, zinc nonanoate, and zinc stearate. The effect of the reactivity and the amount of zinc precursor on nucleation and growth of ZnSe nanocrystals were investigated by ultraviolet-visible absorption and photoluminescence spectra. Result indicates that the growth and optical property of the resulting ZnSe nanocrystals are strongly dependent on the alkyl chain length and the amount of the zinc carboxylates and both shorter alkyl chain length, and more amount of zinc carboxylate will lead to faster growth of ZnSe nanocrystals. This allows that the controlled growth and excellent optical property of high-quality ZnSe nanocrystals can be achieved by combining the different reactivity and the used amount of zinc precursor, such as by using stoichiometric and reactive Zn precursor and Se precursor or by using larger amount of more unreactive Zn precursor relative to the highly reactive alkylamine-H2Se complex precursor.